CONTEÚDOS TEMÁTICOS PARA O DESENVOLVIMENTO DE APLICATIVO MÓVEL SOBRE COVID-19 - Michelly Cristynne Souza Bonifácio; Aline Cerqueira Santos Santana da Silva; Fernanda Garcia Bezerra Góes; Andressa Silva Torres dos Santos; Layanne Fonseca Pinto; Yasminn Canella Cabral Banjar Coelho (Universidade Federal do Paraná, 2021)
Objective: to analyze thematic content about covid-19 for the development of a mobile application for the population, from the perspective of health professionals. Method: qualitative research, developed in the state of Rio de Janeiro, between August and October 2020, through an electronic form with health professionals, whose data were processed in IRAMUTEQ software by the methods: Descending Hierarchical Classification, Correspondence Factor Analysis and Similarity Analysis. Results: the thematic contents identified for the development of the mobile application were protective and behavioral measures, accurate and reliable information on the facts surrounding covid-19, contagion, transmission, as well as information on care locations for the population.  Conclusion: it is concluded that the availability of these contents in a mobile app is more than a facilitator for nurses; it presents itself as a critical component to transform nursing practice and education.